A De novo HDAC2 variant in a patient with features consistent with Cornelia de Lange syndrome phenotype. Issue 5 (25th February 2019) - Wagner, Victoria F.; Hillman, Paul R.; Britt, Allison D.; Ray, Joseph W.; Farach, Laura S.
Abstract : Cornelia de Lange syndrome (CdLS) is an autosomal dominant genetic disorder caused by pathogenic variants in NIPBL, RAD21, SMC3, HDAC8, or SMC1A ; all of which code for proteins that are components of, or interact with, the cohesin complex. Despite the identification of multiple genes associated with CdLS, over 25% of individuals strongly suspected to have CdLS have negative genetic testing, indicating that there are additional genes associated with the condition. HDAC2 codes for histone deacetylase 2 (HDAC2) and, like HDAC8, is a Class 1 histone deacetylase. We present a patient with a novel de novo variant in HDAC2 with many clinical features consistent with CdLS including severe developmental delay, limb abnormalities, congenital heart defect, cryptorchidism and hypoplastic genitalia, growth retardation, and characteristic craniofacial features. Although variants in HDAC2 are not currently associated with human disease, the variant identified in this patient is within a highly conserved amino acid residue and has not been observed in healthy populations. This information, along with the patient's clinical presentation and the functional similarity between the HDAC2 and HDAC8 proteins, suggests that HDAC2 should be further investigated as a candidate gene for CdLS or a CdLS‐like syndrome.